2017
DOI: 10.1371/journal.pone.0170768
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Structural Features of Condensed Tannins That Affect Protein Aggregation

Abstract: A diverse panel of condensed tannins was used to resolve the confounding effects of size and subunit composition seen previously in tannin-protein interactions. Turbidimetry revealed that size in terms of mean degree of polymerisation (mDP) or average molecular weight (amw) was the most important tannin parameter. The smallest tannin with the relatively largest effect on protein aggregation had an mDP of ~7. The average size was significantly correlated with aggregation of bovine serum albumin, BSA (mDP: r = -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 57 publications
7
60
5
Order By: Relevance
“…Nevertheless, besides a positive effect of tannins on reducing diarrhea, previous experiments have failed to show a positive effect of tannins on ETEC shedding [15, 28]. The lack of effects of tannins observed in previous studies is probably related to differences in the bioactivity of tannins according to the dose (1% CE, as previously administered, was not sufficiently high compared to 2% in the present study), as well as to the chemical structure of tannins [32]. However, caution should be taken in using hydrolysable tannins in experiments because up to now, it has been unclear whether the effects of tannins are due to the hydrolysable tannins and/or to their metabolites (ellagic acid and urolithins), as hydrolysable tannins can be hydrolyzed both in the stomach and the gut [33].…”
Section: Discussioncontrasting
confidence: 62%
“…Nevertheless, besides a positive effect of tannins on reducing diarrhea, previous experiments have failed to show a positive effect of tannins on ETEC shedding [15, 28]. The lack of effects of tannins observed in previous studies is probably related to differences in the bioactivity of tannins according to the dose (1% CE, as previously administered, was not sufficiently high compared to 2% in the present study), as well as to the chemical structure of tannins [32]. However, caution should be taken in using hydrolysable tannins in experiments because up to now, it has been unclear whether the effects of tannins are due to the hydrolysable tannins and/or to their metabolites (ellagic acid and urolithins), as hydrolysable tannins can be hydrolyzed both in the stomach and the gut [33].…”
Section: Discussioncontrasting
confidence: 62%
“…In related studies, the DP of CTs has been shown to parallel enzyme inhibition of trypsin, a-amylase and lipase (Horigome et al, 1988) and trypsin (Helsper et al, 1993). Similar decreases in the a-helical/b sheets ratios were observed during the formation of CT-protein complexes of bovine serum albumin (BSA) with a collection of compositionally different CTs (Ropiak et al, 2017). Interestingly, additional studies have shown CT binding to increase the proportion of b sheet at the expense of the a-helical content in the CT-protein complex.…”
Section: Impact Of Condensed Tannin Size On Protein Affinitymentioning
confidence: 76%
“…Examination of the complexation of pancreatic elastase with CT from grape seed (dimer through tetramer CT and an isolated oligomeric fraction of CT) via circular dichroism reveals a decrease in percentage a-helical content with a concomitant increase in percentage b sheet content (Brás et al, 2010). Similar decreases in the a-helical/b sheets ratios were observed during the formation of CT-protein complexes of bovine serum albumin (BSA) with a collection of compositionally different CTs (Ropiak et al, 2017).…”
Section: Impact Of Condensed Tannin Size On Protein Affinitymentioning
confidence: 77%
See 2 more Smart Citations